2017
DOI: 10.1111/avsc.12300
|View full text |Cite
|
Sign up to set email alerts
|

Resprouting of woody species encroaching temperate European grasslands after cutting and burning

Abstract: Questions: Are there interspecific differences in resprouting after cutting and burning among woody species encroaching temperate grasslands? Are alien woody species more successful than natives in their resprouting after the two treatments proposed to control shrub encroachment? Is resprouting influenced by age of the individuals? Does resprouting differ between cutting and burning?Location: Temperate grasslands encroached by shrubs, Transylvania, Romania. Methods:We investigated the resprouting after cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Alongside the expansion of native woody species, e.g., Cornus sanguinea or Crataegus monogyna , into Transylvanian grassland (Sărăţeanu, Moisuc, Butnariu, & Stroia, ), woody species non‐native to the Transylvanian region were also introduced (Michielsen, Szemák, Fenesi, Nijs, & Ruprecht, ). In the study area, the most widespread of these species is Hippophae rhamnoides , which is regarded as a threat to local biodiversity (Michielsen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the expansion of native woody species, e.g., Cornus sanguinea or Crataegus monogyna , into Transylvanian grassland (Sărăţeanu, Moisuc, Butnariu, & Stroia, ), woody species non‐native to the Transylvanian region were also introduced (Michielsen, Szemák, Fenesi, Nijs, & Ruprecht, ). In the study area, the most widespread of these species is Hippophae rhamnoides , which is regarded as a threat to local biodiversity (Michielsen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance type (mowing versus burning) had a limited effect on resprouting dynamics of scrubby flatwoods shrub species. Similarly, many studies have found little difference in resprouting or woody cover after burning versus mowing or cutting or clipping (e.g., Hmielowski et al 2014;Peterson and Drewa 2014;Michielsen et al 2017). In contrast, some studies have found that burning results in higher mortality and lower post-disturbance growth than cutting (Peguero and Espelta 2011;Noble and Diggle 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the effects of disturbances on resprouting commonly include clipping aboveground plant parts (e.g., Cruz et al 2003;Schafer and Just 2014;Martinez-Vilalta et al 2016). If the main effect of repeated loss of aboveground biomass is carbohydrate starvation, then clipping and burning should have similar effects on resprouting (Hmielowski et al 2014;Michielsen et al 2017). If resprouting responses are stronger in relation to fire than clipping (e.g., Peguero and Espelta 2011;Noble and Diggle 2014), this could be attributed to the positive effects of nutrient fertilization from ash, loss of nutrients through volatilization, or direct effects of heat on bud banks.…”
Section: Introductionmentioning
confidence: 99%
“…Third, several Non-Governmental Organizations also increased the social awareness about the decline of biodiversity (especially in the protected areas but also beyond) (Rozylowicz et al 2017), this again motivating research targeting the biodiversity and conservation of grasslands. Within this, the mountain hay meadows have outstanding importance (this is why ‘Carpathians’ were highlighted as important, Figures 8 and 9), being highly biodiverse as well as threatened by overgrazing and abandonment (Cremene et al 2005, Sutcliffe et al 2014, Michielsen et al 2017). A relatively recent overview of the research targeting Natura 2000 sites in the European Union showed that research supporting Natura 2000 network is dominated by ecological research while the policy and social aspects are underrepresented (Popescu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The intensive, highly specialized management of the grasslands resulted in the sharp decrease in their biodiversity, aesthetic and cultural values or even the disappearance of the grasslands. On the other hand, land abandonment also threatens several species and habitats (however also creating opportunities for conserving others) as well as ecosystem services of grasslands, commonly through woody vegetation encroachment (Stoate et al 2009, Bugalho et al 2011, Queiroz et al 2014, Michielsen et al 2017).…”
Section: Introductionmentioning
confidence: 99%